Mass islamization of peasants in Bosnia: Demystifications - Moačanin, Nenad (1999)
Bosnian peasants have adopted islam en masse mainly as a consequence of the poorly developed food production. That fact has not been perceived as yet but in random remarks. Narrative and archival sources supporting this idea are abundant.
Projekt MZOS
ENG